2010
DOI: 10.5152/akd.2010.08
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Use of Leflunomide as a Cause of Severe Diarrhea?

Abstract: Abst ractLeflunomide is a recently developed disease modifying antirheumatic drug that may cause acute diarrhea as an adverse effect. This adverse effect is usually mild and develops during the first few weeks of treatment. In this report, we present a case of rheumatoid arthritis patient with severe diarrhea treated with leflunomide for an extended period of time. (Turk J Rheumatol 2010; 25: 41-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…As such, the current mainstay for diagnosis appears to also be its treatment: symptomatic improvement after medication cessation. [1][2][3] This case demonstrates an example of leflunomide-induced colitis which should be considered in patients who present with symptoms of abdominal pain and diarrhea in the setting of leflunomide use, even months to years after medication initiation.…”
Section: Answer To: Image 3 (Page 2034): Drug-induced Colitis Secondamentioning
confidence: 98%
“…As such, the current mainstay for diagnosis appears to also be its treatment: symptomatic improvement after medication cessation. [1][2][3] This case demonstrates an example of leflunomide-induced colitis which should be considered in patients who present with symptoms of abdominal pain and diarrhea in the setting of leflunomide use, even months to years after medication initiation.…”
Section: Answer To: Image 3 (Page 2034): Drug-induced Colitis Secondamentioning
confidence: 98%
“…These adverse effects may complicate their long-term use in other immune-related conditions. For instance, while leflunomide has shown efficacy in CD, its adverse effect of diarrhea is not acceptable in an IBD patient population [22]. In the COMPONENT study, neither diarrhea nor alopecia were observed at a higher rate as a consequence of therapy with vidofludimus compared with placebo.…”
Section: Off-target Effects: Diarrhea Alopecia and Neutropeniamentioning
confidence: 99%
“…While leflunomide is widely used in treating RA, either as a monotherapy or in combination with methotrexate [18], the class of DHODH inhibitors to which both leflunomide and teriflunomide belong have been the subject of numerous safety concerns since their approval by the FDA. Postmarket surveillance includes reports of a variety of drug-related adverse reactions, including elevated liver enzymes and hepatotoxicity, peripheral neuropathy, vasculitis, hypertension, alopecia, pruritus, nausea, and diarrhea [16,[19][20][21][22][23][24][25][26][27][28]. In one prospective study evaluating leflunomide treatment in 136 RA patients, 65% of patients experienced at least that inhibitors of DHODH show immunomodulatory activity, which is most pronounced on T cells [3][4][5][6][7][8], with T helper (Th) 1 and Th17 cells acting as important contributors to the inflammatory processes of RA [9].…”
Section: Key Pointsmentioning
confidence: 99%